Reduced chemical weathering intensity in the Qaidam Basin (NE Tibetan Plateau) during the Late Cenozoic. (February 2019) - Bao, Jing; Song, Chunhui; Yang, Yibo; Fang, Xiaomin; Meng, Qingquan; Feng, Ying; He, Pengju
Graphical abstract: Highlights: Detailed 15.3–1.8 Ma clay elemental geochemistry records for the northeastern Qaidam Basin are presented. Long-term and persistent weakening of the chemical weathering intensity has occurred since the Middle Miocene. Global cooling-related drying played a key role in the chemical weathering intensity. Miocene uplift of the northern Tibetan Plateau might exert some influence on the weakened chemical weathering intensity at 12–8 Ma. Abstract: Cenozoic basin sediments around the Tibetan Plateau are valuable archives that can be used to reveal long-term interactions among tectonics, climate and weathering. However, the reconstruction of silicate weathering histories in this tectonically active region is consistently hindered by the presence of frequently embedded conglomerate and sandstone in the long sedimentary sequences. Here, we present detailed geochemical compositions of the clay components of the sediments in the Huaitoutala section (ca. 15.3–1.8 Ma) of the northeastern Qaidam Basin to reconstruct the chemical weathering history of the catchment since the Middle Miocene. Major element ratio proxies reveal evidence of four stages of change: from ca. 15.3 to 12.6 Ma, in which the clay components are characterized by relatively high Chemical Index of Alteration (CIA) values (75–88, average = 81) but low mobile/immobile oxide ratios (e.g., K2 O/Al2 O3, Na2 O/Al2 O3 and CaO/Al2 O3 ), thus indicating the occurrence of intense chemical weathering conditions; from ca. 12.6 to 6.6 Ma, in which decreasing CIA values, together with increasing mobile/immobile oxide ratios, suggesting that a long-term decrease in silicate weathering intensity occurred in the source area; from 6.6 to 2.6 Ma, in which the clay components in the sediments exhibit persistently low CIA values (66–81, average = 76.8) and high oxide ratios, which are indicative of mild to moderate chemical weathering; and since 2.6 Ma, in which the CIA values (64–80, average = 75.5) have continued to decrease with increasing oxide ratios, thus reflecting mild chemical weathering conditions. The geochemical proxy records demonstrate that the intensity of chemical weathering has continually decreased and that the Qaidam Basin has experienced continuous aridification since ca. 12.6 Ma. We suggest that Middle-Miocene global cooling-related drying has exerted a significant influence on the trend of decreasing chemical weathering intensity since ca. 12.6 Ma. In addition, the Late Cenozoic rapid uplift and exhumation of the NE Tibetan Plateau could have limited the time that the silicate rocks were exposed in the weathering profile prior to the deposition, which may have led to their weakened intensity of chemical weathering.